Cyclically Adjusted Provisions and Financial Stability - Pierre-Richard Agénor; Luiz A. Pereira da Silva (Inter-American Development Bank (IDB), 2016)
This paper studies the extent to which alternative loan loss provisioning regimes affect the procyclicality of the financial system and financial stability. It uses a DSGE model with financial frictions (namely, balance sheet and collateral effects, as well as economies of scope in banking) and a generic formulation of provisioning regimes. Numerical experiments with a parameterized version of the model show that cyclically adjusted (or, more commonly called, dynamic) provisioning can be highly effective in terms of mitigating procyclicality and financial instability, measured in terms of the volatility of the credit-output ratio and real house prices, in response to financial shocks. The optimal combination of simple cyclically adjusted provisioning and countercyclical reserve requirements rules is also studied. The simultaneous use of these instruments does not improve the ability of either one of them to mitigate financial instability, making them partial substitutes rather than complements.
hdl:11319/7619
Keywords: E32; E44; E52; 330; Provisioning regimes; Reserve requirements; DSGE models